The Influence of Product Design, Price and Online Marketing Communication on Purchasing Decisions - Pelupessy, Merry; Maiseka, Gresia (Jurnal Ekonomi, 2024)
This study aims to determine the effect of product design, price and online marketing communication on purchasing decisions for woven fabrics at the Glora store in Tatumbar Islands Regency. This study is a survey study using a quantitative method, so the number of samples determined is 115 respondents who are consumers of Toku Gluta products. To collect research data using a questionnaire and distributed via Google Form, and Bu data analysis using descriptive analysis and multiple linear regression analysis. Based on our analysis, this research proves that product design does not have a graphical effect on purchasing decisions, Price does not have a significant effect on purchasing decisions, Online marketing communication has a negative effect on purchasing decisions for woven fabrics at Glora Store in Tatumbar Islands Regency.